Rancang Bangun Aplikasi Teknik Dasar Taekwondo Menggunakan Animasi 3D Berbasis Android - Anton Sandra; Irwan Adi Pribadi; Rizky Prabowo; Ossy Dwi Endah Wulansari (Department of Computer Science, Faculty of Mathematics and Natural Sciences, University of Lampung, 2023)
Taekwondo, essentially a form of self-discipline and a martial art utilizing techniques with bare feet and hands, originated as a ceremonial practice in Korean culture. Over time, it transformed into a crucial self-defense system for Korean warriors. In the contemporary context, Taekwondo has become widely popular, attracting individuals eager to learn but hindered by a lack of foundational knowledge. The application developed in this study serves as a valuable resource for users to grasp the fundamental movements of Taekwondo, encompassing kicks, punches, stances, and techniques. This initiative aims to make the learning process more accessible, allowing individuals to engage with Taekwondo lessons conveniently at any time and from any location. The research involves a collaborative effort with a Taekwondo instructor affiliated with the State Polytechnic Lampung, ensuring the incorporation of authentic martial arts knowledge into the application.